1995
DOI: 10.1007/bf00400723
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of IDDM during 1988–1992 in Zagreb, Croatia

Abstract: SummaryThe objective of this study was to determine the incidence of insulin-dependent diabetes mellitus (IDDM) in the population of Zagreb, Croatia, during 1988Croatia, during -1992. A centralized diabetes registry was the primary source of data, while secondary sources were used to assess ascertainment. A total of 282 new cases of IDDM were diagnosed in the study period, the primary and secondary sources identifying annually 93-100 % of the cases. The annual incidence rate ranged from 5.6 per 100,000 to 6.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Among many reports that connected psychological stress with the emergence of type 1 diabetes (mostly questionnaire‐based studies) , two studies have identified the trauma of war in the republics of former Yugoslavia as one of the severe stressful events that were associated with the emergence of the disease . In contrary, no change in diabetes incidence was found during the war in Croatia . Many studies that addressed the effect of psychological stress on type 1 diabetes were conducted on a small scale.…”
Section: Discussionmentioning
confidence: 99%
“…Among many reports that connected psychological stress with the emergence of type 1 diabetes (mostly questionnaire‐based studies) , two studies have identified the trauma of war in the republics of former Yugoslavia as one of the severe stressful events that were associated with the emergence of the disease . In contrary, no change in diabetes incidence was found during the war in Croatia . Many studies that addressed the effect of psychological stress on type 1 diabetes were conducted on a small scale.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported a strong male preponderance in the incidence of Type 1 diabetes in adults [18,19,20,21,22,23,24,25,26,27]. In this respect young adults differ from children, for overall sex-specific differences in children are slight, although high-incidence populations tend to show male preponderance, and low-incidence populations (mostly non-European) show female preponderance [34].…”
Section: Discussionmentioning
confidence: 99%
“…Adult cases are characterised by a reduced frequency of HLA susceptibility haplotypes, as compared with children [1,16,17], and overall have less acute symptoms than children [1]. Male predominance is a further, unexplained feature of Type 1 diabetes in young adults [18,19,20,21,22,23,24,25,26,27]. This is in marked contrast to most other common immune-mediated conditions, which are typified by female preponderance [28].…”
mentioning
confidence: 99%
“…A male excess is found primarily among Caucasoid populations, where the high incidence of IDDM is prevailing. Only a limited number of studies of IDDM incidence (all in Europid populations) have been done among young adults in the 15-39 year age group, 38,62,69,70,73,[84][85][86] and almost all of them have reported a strong male excess in the incidence of IDDM. This age-related difference in the sex ratio is an interesting phenomenon but difficult, however, to interpret from the epidemiological point of view since the existing data are scarce.…”
Section: Discussionmentioning
confidence: 99%